Gobak sodor as a culturally grounded motivational framework: effects of traditional game-based learning on engagement and achievement in junior high school physical education - Qisthosyi Qurnul Isyrin; Advendi Kristiyandaru; Himawan Wismanadi (Indonesian Institute for Counseling, Education and Theraphy, 2026)
Low motivation and poor learning outcomes represent persistent challenges in Physical Education, Sports, and Health (PJOK) instruction at the junior high school level, yet the motivational mechanisms underlying culturally grounded pedagogical interventions remain underexplored. Grounded in Self-Determination Theory (SDT), this quasi-experimental study examines whether the integration of the traditional Indonesian game Gobak Sodor into PJOK instruction is associated with improved student motivation and learning outcomes among seventh-grade students at SMP Negeri 2 Tulangan. A pretest-posttest control group design was employed, with 31 students in an experimental group receiving eight sessions of Gobak Sodor-based instruction and 31 students in a control group receiving conventional teaching methods. Learning motivation was assessed using a validated Likert-scale questionnaire (Cronbach’s α = 0.862), and learning outcomes were measured via achievement tests. Results indicated a substantially greater increase in mean achievement scores in the experimental group (68.35 to 88.42) compared to the control group (66.94 to 70.03), with a statistically significant between-group difference at posttest (t = 26.674; p < 0.001). Motivation scores also increased significantly in the experimental group (p < 0.001), suggesting that SDT-aligned conditions of autonomy, competence, and relatedness may explain the observed engagement gains. However, given the quasi-experimental design, non-random class assignment, and single-school sample, causal inferences are constrained; findings should be interpreted as preliminary evidence warranting replication in broader and more diverse contexts.